GAMBARAN TINGKAT PENGETAHUAN TENTANG MENYIKAT GIGI PADA SANTRI (Jurnal Kesehatan Siliwangi, 2020)
Brushing is a procedure that makes the necessity because the toothbrush is a tool to clean the teeth of the leftover food and plaque attached to the tooth surface. Uncleaned plaque will grow thicker when the calcification will become Tartar, maintenance of improper dental health that can cause problems for the health of the teeth and mouth. This research is a descriptive study. The purpose of this research is to know the idea of the level of knowledge about brushing teeth in the students of Pesantren Engg Ulum. This research is done by filling the questionnaire by taking samples using Probability Sampling, so that the sample 32 people obtained. The results of the study showed a level of knowledge with good criteria of 34.4%, sufficient criteria of 9.3% and criteria less 56.3%. Thus it can be concluded that the students of the boarding school Engg Ulum Parongpong is still lacking in the knowledge brushing well and correct teeth. Key words:Knowledge of brushing, students